Resting heart rate variability is associated with inhibition of conditioned fear - Wendt, Julia; Neubert, Jörg; Koenig, Julian; Thayer, Julian F.; Hamm, Alfons O. (Psychophysiology, 2015)
Startle blink as well as skin conductance responses (SCR) are widely used indices of learning processes associated with fear conditioning and extinction. During safety learning, the amygdala is under top-down inhibitory control by the prefrontal cortex (PFC). The capacity of the PFC to exert inhibitory control over subcortical brain structures may be indexed by resting state vagally mediated heart rate variability (HRV). The present study investigated the association of resting HRV with startle blink and SCR during conditioned fear inhibition and extinction. Participants first learned to discriminate a threat cue (A) signaling an aversive unconditioned stimulus from a safety signal (B), which were each presented together with a third stimulus X (AX+/BX−). Then, both the threat and safety signal were presented together (AB) to test whether the presence of the learned safety signal inhibits the fear response to the danger signal. Finally, AX was presented without reinforcement (AX−) to investigate fear extinction. Higher HRV was associated with pronounced fear inhibition and fear extinction. Resting HRV levels were associated with fear extinction as indexed by startle blink potentiation but not SCR, which presumably reflect more cognitive aspects of learning. Resting HRV may reflect the capacity of the prefrontal cortex to inhibit subcortical fear responses in the presence of safety or when former threat cues are presented in the absence of threat.
Gesehen am 30.06.2020